Current characteristics of λ-DNA molecules/polystyrene nanoparticles in TBE buffer solution through micro/nanofluidic capillaries under DC electric field. (23rd February 2017) - Duan, Yifei; Zhao, Wei; Xue, Jing; Sun, Dan; Wang, Kaige; Wang, Guiren; Li, Junjie; Bai, Jintao; Gu, Changzhi
Abstract: In practical applications of biochips and bio-sensors, electrokinetic mechanisms are commonly employed to manipulate single bio-molecules and analyze their characteristics. To accurately and flexibly control the movement of single-molecule within micro/nanofluidic channels which are the basic components of Lab-chips, the current signals in micro/nanocapillaries filled with solutions of DNA molecules or polystyrene (PS) nanoparticles are systematically studied. Experimental results indicate that the current response along the micro/nanocapillaries can be significantly influenced by the diameter of the capillaries and the pH value of the solutions. Specifically, when there is only a pure (TBE) solution, the electric conductance does not monotonically decrease with decreasing the diameter of the capillaries, but slightly increases with decreasing the capillary diameter. When λ -DNA molecules or PS nanoparticles are added into the TBE buffer, the size effect on the electric conductance of the solutions are quite different. Although in the former, the electric conductance behaves differently from that in the pure TBE solution and decreases with the decreasing diameter, in the latter, the change is similar to that in the pure TBE solution. Besides, an abnormal 'falling' of the electric conductance is observed in a capillary with diameter of 200 nm. The investigation will significantly enhance the understanding on the electric properties of the solutions of biomolecules and particles in micro/nanofluidics. This is especially helpful for designing functional Lab-chip devices.